Pengaruh Service Recovery Terhadap Kepuasan Konsumen Pada Hotel Rama Candidasa - Ni Wayan Suartini Ningsih; Ni Made Yudhaningsih (Jurnal Ilmiah Satyagraha, 2019)
As a hospitality business can not be separated from error or service failure. so companies need to handle the failure of the service with service recovery program embodied with three dimensions of procedural justice, interactional justice and distributive justice. This study aims to Determine the influence of procedural justice, interactional justice distributive justice on customer satisfaction at Rama Candidasa Hotel. This study used 80 samples, the method of collecting data through questionnaires. Data analysis was performed with multiple linear regression analysis,test f  test t and the previous determination has been tested the validity and reliability.The results showed by the F-test is procedural justice, interactional justice and distributive justice have positive and significant impact on customer satisfaction at Rama Candidasa Hotel. From the results of correlation analysis this shows thata positive and very powerful relationship between procedural justice, interactional justice and distributive justice with customer satisfaction. Where the condition shows the higher the value of procedural justice, interactional justice and distributive justice, that make the higher the value of customer satisfaction and same as the other way. From result of determination analysis (R2) obtained coefficient of determination equal to 64,4%, which means that customer satisfaction is true result from influence of procedural justice, interactional justice and distributive justiceequal to 64,4%, while 35,6% influenced by other factor. Furthermore, based on T-test results obtained that the distributive justice has greater influence and stronger than procedural justice and interactional justice.